Perancangan Sistem Monitoring Tegangan, Arus Dan Frekuensi Pada Pembangkit Listrik Tenaga Mikrohidro Berbasis IoT - Yohanes P Simanjuntak; Beni Satria; Amani Darma Tarigan (CV. Hawari, 2026)
Hydropower plants (PLTA) remain the largest contributor to renewable energy generation capacity in Indonesia. As of October 2025, renewable energy generation capacity was recorded at 15,446.85 MW, with hydro contributing 6,539.17 MW and micro-hydro contributing 976.18 MW. Many micro-hydro locations operate in areas with limited access, so routine generator output checks are still often carried out through periodic visits to the location. Field observations reported in previous studies show that output conditions can fluctuate widely when there are load changes, including voltages from 160 V to 235 V and frequencies from 44 Hz to 51 Hz, which can potentially affect service quality and equipment operation. This study designed and implemented an Internet of Things (IoT)-based monitoring system to measure and report generator output voltage, load current, and frequency in real-time. The prototype integrates an ESP32 microcontroller, an AC energy measurement module, a local LCD display, and a cloud dashboard for remote visualization and time-stamped logging. The polling and transmission processes in the firmware are configured with a 5-second sampling interval to capture the dynamics caused by load changes while maintaining stable data delivery. Performance evaluation includes calibration against reference instruments, measurement of data update latency from acquisition to display on the dashboard, and tracking of transmission reliability through upload outcomes. The results of the study demonstrate a practical monitoring architecture, improve data availability for operators, and support operational decision-making without relying on frequent site visits.